Self-reported Treatment Goals in Chinese Patients with Inflammatory Bowel Disease During the Coronavirus Disease 2019 Pandemic - Tian, Wen-Ning; Huang, Yu-Hong; Jiang, Min; Dai, Cong (Turkish Journal of Gastroenterology, 2022)
Background: Inflammatory bowel disease is a chronic recurrent disease, and the treatment goals of inflammatory bowel disease are mainly based on doctors’ perspective, but there are some differences between the doctor’s perspective and the patient’s perspective. The aim of this study is to understand the treatment goals and the related factors from the patients’ perspective during the coronavirus disease 2019 pandemic. Methods: A total of 212 participants were recruited to fill out the questionnaires including clinical characteristics and treatment goals. Eleven treatment goals were measured by a Short-Form 34 questionnaire. Univariate and multivariate regression analyses were used to explore the related factors about these treatment goals. Results: A total of 212 inflammatory bowel disease patients were enrolled in this study. The most concerned treatment goal was the improvement of quality of life (mean score was 8.54), while mean score of ulcerative colitis patients and Crohn’s disease patients was 9.10 and 8.45, respectively. We had also found some related factors such as the type of disease, the course of disease, the frequency of hematochezia, and defecation. Conclusion: Our survey showed that inflammatory bowel disease patients pay more attention to the improvement of quality of life and few drugs during the coronavirus disease 2019 pandemic. There are some related factors such as the type of disease, the course of dis- ease, the frequency of hematochezia, and defecation. Our results help clinicians understand the patients’ treatment goals, which can contribute to better management of inflammatory bowel disease patients. Cite this article as: Tian W, Huang Y, Jiang M, Dai C. Self-reported treatment goals in Chinese patients with inflammatory bowel disease during the coronavirus disease 2019 pandemic. Turk J Gastroenterol. 2022;33(7):554-564.